Genetic liability to schizophrenia measured by P300 in concordant and discordant monozygotic twins - Sharma, Anuradha; Sauer, Heinrich; Smit, Dirk J. A.; Bender, Stephan; Weisbrod, Matthias (Psychopathology, 2011)
Background: Differential effects of genes and environment can contribute to etiological heterogeneity in schizophrenia. Twins concordant and discordant for schizophrenia may differ in genetic predisposition to schizophrenia with concordant twins having a higher genetic liability and discordant twins having a lower genetic liability to schizophrenia. We aimed to investigate whether P300 amplitude (which has been postulated as a genetic marker for schizophrenia) reflected this heterogeneity. Sampling and Methods: We compared P300 amplitudes across 36 monozygotic twin pairs (6 concordant for schizophrenia/schizoaffective disorder, 11 discordant and 19 healthy control pairs) performing an auditory oddball task, using multiple regression (age, gender, birth order, premorbid IQ as covariates). We further looked at the correlation between the Brief Psychiatric Rating Scale (BPRS) and P300 amplitude in affected twins, and compared concordant and discordant affected twins on the Global Assessment Scale (GAS). Results: Multiple regression yielded a highly significant model (p = 0.004) though the explained variance was limited (21%). The main effect of the group on P300 amplitude was significant (p = 0.0001): affected concordant twins showed a significantly lower P300 amplitude as compared to affected discordant (p = 0.005, Cohen’s d = 1.08) and control twins (p = 0.000, d = 1.16). Discordant affected and unaffected twins did not differ significantly from each other or from control twins. P300 did not correlate significantly with the BPRS and the affected groups did not differ across the GAS. Conclusions: Our results provide evidence for etiological heterogeneity within schizophrenia pointing to different pathophysiological mechanisms that may underlie more and less genetically determined forms of schizophrenia. They also indicate that P300 correlates with a differing degree of genetic liability to schizophrenia independently of the psychopathological status and even in the presence of similar functional profiles.
Gesehen am 30.11.2022